Design and validation of a hybrid interactive reference point method for multi-objective optimization - Sathe, M.; Rudolph, G.; Deb, K. (2008 IEEE Congress on Evolutionary Computation (IEEE World Congress on Computational Intelligence), 2008)
This paper offers a classification of the main representatives of interactive classical and evolutionary methods. After a crossfertilization of these two fields a new hybrid interactive reference point method is designed. The method combines the reference point idea with the relative speed of a (1+1) - EA and is implemented with a graphical user interface. Finally, it is validated on two well-known real-world test problems.